Eksplorasi Nilai Pendidikan Lingkungan Cerpen Daring Republika: Kajian Ekokritik - Juanda Juanda Juanda (JURNAL SOSIAL HUMANIORA (JSH), 2018)
The purpose of this study is to explore the value of environmental education and interaction between characters and nature in the short stories of the Republika newspaper. The author describes the form of ecological criticism and interaction between characters and the environment as a form of ecological criticism in the short story in the Republika newspaper. This type of research is qualitative research with an ecocritical approach. The method used is descriptive to describe ecological criticism in environmental education and interaction of characters with the environment in the short story. The data of this study are sourced from the short stories of the Republika newspaper downloaded from laconhidup.com. There are five ecocritical short stories, namely: Son of Only Wood author Riki Eka, short story, Republika January 13, 2013; short story A Muttaqin Leaf Sheet, Republika 4 August 2013; short story Yudhi Herwibowo Golden Tree, Republika May 11, 2014, Eni Wulansari's short story Trembling Steps, Republika August 23, 2015; and Short Time Zhizi Siregar Short Story ", Republika January 25, 2018. The data were analyzed using an ecocritical approach Grag Garrard (2004): pollution, forests, natural disasters, settlements, living things, and the earth. Of the five short stories found 45 data relating to the formulation of research problems. Data which is a form of ecological criticism is 31 data. Data that describes the form of interaction between characters and nature amounts to 14 data, which is divided into 3 forms of interaction, namely observation of characters with the environment,  an attitude of characters, actions of characters, and thoughts of characters. The value of Republika's short story environmental education, namely: tree planting, reforestation of forests that have been exploited, the implementation of rules and regulations for deforestation, and animal conservation.